Factors influencing intentions to use QRIS: A two-staged PLS-SEM and ANN approach - Rizka Ramayanti; Zubir Azhar; Nik Hadian Nik Azman (Telematics and Informatics Reports)
This study investigates the factors influencing users' intention to utilise Indonesia's Quick Response Code Indonesian Standard (QRIS). It employed a questionnaire survey with 996 QRIS users in Indonesia as respondents, with response rate 95. 95 %. This study analysed the data using the structural equation modelling – artificial neural network (SEM-ANN) approach. The data were evaluated using SmartPLS 4.0 and SPSS 26 for artificial neural network (ANN) analysis. The SEM analysis suggests that Habit, Hedonic Motivation, Social Influence, and Price Value are the primary factors influencing QRIS intention and usage in Indonesia. Performance expectancy, effort expectancy, and facilitating factors are not significantly related to users' intention to use QRIS. User intention significantly influences the actual usage of QRIS. The importance-performance matrix analysis (IPMA) test indicates that hedonic desire is the most significant factor in predicting the intention to use QRIS compared to other variables. The findings demonstrated that hedonic motivation was the primary determinant in forecasting the intention to use QRIS.